Use of corn maze educational game as a learning medium for rural communities to build food security behaviours. Issue 1 (March 2021) - Pujiastuti, H; Haryadi, R
Abstract: The purpose of this study is to develop food security behaviours in rural communities. The place of this research was conducted in the village of Banyubiru, Labuan district, Pandeglang regency, Banten Province, Indonesia. The method used in this study was an experiment with the design of forming three village community groups, each group consisting of 15 people. The instrument used in this study was a food security behaviours questionnaire test and an observation sheet during the implementation of the corn labyrinth educational game. The results of the questionnaire of resistance behaviours in the village community in Labuan Banten amounted to 66.83% or 0.67 in the good category. Furthermore, the observations during using the labyrinth educational game of 72.50% or 0.73 are in the good category. So it can be concluded that the behaviours of food security can be grown through learning activities through the design of a corn maze educational game.